The effect of acidic pH on the adsorption and lytic activity of the peptides Polybia-MP1 and its histidine-containing analog in anionic lipid membrane: a biophysical study by molecular dynamics and spectroscopy - Martins, Ingrid Bernardes Santana [UNESP] (2021)
Antimicrobial peptides (AMPs) are part of the innate immune system of many species. AMPs are short sequences rich in charged and non-polar residues. They act on the lipid phase of the plasma membrane without requiring membrane receptors. Polybia-MP1 (MP1), extracted from a native wasp, is a broad-spectrum bactericide, an inhibitor of cancer cell proliferation being non-hemolytic and non-cytotoxic. MP1 mechanism of action and its adsorption mode is not yet completely known. Its adsorption to lipid bilayer and lytic activity is most likely dependent on the ionization state of its two acidic and three basic residues and consequently on the bulk pH. Here we investigated the effect of bulk acidic (pH 5.5) and neutral pH (7.4) solution on the adsorption, insertion, and lytic activity of MP1 and its analog H-MP1 to anionic (7POPC:3POPG) model membrane. H-MP1 is a synthetic analog of MP1 with lysines replaced by histidines. Bulk pH changes could modulate this peptide efficiency. The combination of different experimental techniques and molecular dynamics (MD) simulations showed that the adsorption, insertion, and lytic activity of H-MP1 are highly sensitive to bulk pH in opposition to MP1. The atomistic details, provided by MD simulations, showed peptides contact their N-termini to the bilayer before the insertion and then lay parallel to the bilayer. Their hydrophobic faces inserted into the acyl chain phase disturb the lipid-packing.